A member of the Tlr family is involved in dsRNA innate immune response in Paracentrotus lividus sea urchin. Issue 2 (August 2015) - Russo, Roberta; Chiaramonte, Marco; Matranga, Valeria; Arizza, Vincenzo
Highlights The expression of a newly isolated Pl-Tlr cDNA is up-regulated after polyI:C challenge (viral infection). Pl-Tlr is down-regulated in LPS injury (bacterial infection) in P. lividus sea urchin immune cells. Phylogenetics of Pl-Tlr and Tlr proteins from vertebrates and invertebrates shows the conservative evolutionary process of these proteins.